Apakah Bermain Lego dan Finger Painting Efektif Mengukur Perkembangan Motorik Halus anak Berkebutuhan Khusus? - Padila Padila; Juli Andri (Jurnal Keperawatan Silampari, 2023)
This study aims to compare the effectiveness of playing Lego with finger painting on the fine motor development of children with special needs at SLBN 1 Bengkulu City. This type of research is quantitative research with a quasi-experimental design. The results of the Wilcoxon test showed that the respondents who were given the intervention to play Lego obtained p-value = 0.09 > 0.05, so there was no effect of the intervention to play Lego on the fine motor development of children with special needs. In contrast, the respondents who were given the intervention to play finger painting obtained p- value = 0.01 <0.05, so playing finger painting intervention has an effect on the fine motor development of children with special needs. Based on the results of the Mann-Whitney test showed that the respondents who were given the intervention to play Lego obtained p-value = 0.21 > 0.05, so there was no effect of the intervention to play Lego on the fine motor development of children with special needs. In contrast, the respondents who were given the intervention to play finger painting obtained p-value = 0.04 <0.05, so playing finger painting intervention has an effect on the fine motor development of children with special needs. In conclusion, the two interventions were statistically effective in increasing the average score of the fine motor skills category of children with special needs, and there was no significant difference in the effectiveness of the two intervention groups in increasing the average score of the fine motor skills category of children with special needs at SLBN 1 Bengkulu City. Keywords: Finger Painting, Lego, Fine Motoric